Electrodeposited gels prepared from protein alloys. (March 2015) - Lin, Yinan; Wang, Siran; Chen, Ying; Wang, Qianrui; Burke, Kelly A; Spedden, Elise M; Staii, Cristian; Weiss, Anthony S; Kaplan, David L
Aim: Silk-tropoelastin alloys, composed of recombinant human tropoelastin and regenerated Bombyx mori silk fibroin, are an emerging, versatile class of biomaterials endowed with tunable combinations of physical and biological properties. Electrodeposition of these alloys provides a programmable means to assemble functional gels with both spatial and temporal controllability.Materials & methods: Tropoelastin-modified silk was prepared by enzymatic coupling between tyrosine residues. Hydrogel coatings were electrodeposited using two wire electrodes.Results & discussion: Mechanical characterization and in vitro cell culture revealed enhanced adhesive capability and cellular response of these alloy gels as compared with electrogelled silk alone.Conclusion: These electro-depositable silk-tropoelastin alloys constitute a suitable coating material for nanoparticle-based drug carriers and offer a novel opportunity for on-demand encapsulation/release of nanomedicine.